Application of Graph Theory in Social Media - Chakraborty, Anwesha; Dutta, Trina; Mondal, Sushmita; Nath, Asoke (International Journal of Computer Sciences and Engineering, 2025)
A graph is made up of nodes; just like that a social media is a kind of a social network, where each person or organization represents a node. These nodes in a social media are interdependent on each other via common interests, relations, mutual friends, knowledge, common dislikes, beliefs etc. The overall graphical structure of a social media can be very complex with millions of nodes and thousands of interconnections amongst them based upon various grounds. Many researchers have revealed that social network works on various levels and helps in understanding many things such as how an entire organization is run. It helps to solve and understand many critical problems. The analysis of the social media is a very useful tool for extracting knowledge from unstructured data. The knowledge obtained from this field provides a vivid knowledge of various kinds interactions and relations amongst various individuals on social media. The authors have elaborated on the various applications of graph theory on social media and how it is represented viz. strong and weak ties. [1]